OBJN Databases and Scholar Links - Isabel C.F. da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2005)
The databases wre the OBJN is indexed and links to universities where the OBJN has a bookmark.